THE INFLUENCE OF SERVICE QUALITY, FACILITIES AND PRICE ON PASSANGER SATISFACTION AT BANDAR SRI JUNJUNGAN DUMAI - RUPAT - Sahadah, Nur; Atman Maulana, Hutomo (LPPM Universitas Malikussaleh, 2024)
This study aims to determine the effect of service quality, facilities and prices on passenger satisfaction at the port of Bandar Sri Junjungan Dumai. The sample objects in this study are people who have used the services of the Bandar Sri Junjungan port in the city of Dumai. This study used a quantitative method using the sample technique in this study as many as 100 respondents, data processing using the SPSS 26 application with multiple linear regression analysis testing which included validity tests, reliability tests, T tests, F tests and the coefficient of determination (R2). The results showed that: 1) service quality had no positive and significant effect on service quality at Bandar Sri Junjungan Dumai port, 2) facilities had no positive and significant effect on passenger satisfaction at Bandar Sri Junjungan Dumai port, 3) price had a positive and significant effect on passenger satisfaction at the port of Bandar Sri Junjungan Dumai 4) the determinant coefficient (R2) is 0.543. This means that the quality of service, facilities and price variables affect passenger satisfaction by 54.3% while the remaining or 45.7% is influenced by other variables not examined in this study.